Adsorption of Fluoroquinolones Antibiotics on Activated Carbon by K2CO3 with Microwave Assisted Activation - Abbas, Ammar S.; Ahmed, Muthana J.; Darweesh, Teeba M. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The preparation of low cost activated carbon from date stones and microwave method by using K2CO3 as chemical activator were investigated. The prepared activated carbon was used to remove fluoroquinolones antibiotics from aqueous solution. The characterizations of the activated carbon is represented by surface area, pore volume, ash content, moisture content, bulk density, and iodine number. The adsorbed fluoroquinolones antibiotics are Ciprofloxcin (CIP), Norfloxcin (NOR) and Levofloxcin (LEVO). Different variables as pH, initial concentrations and contact time were studied to show the efficieny of prepared activated carbon. The experimental adsorption data were analyzed by Lungmuir, Freundlich, and Temkin isotherm. The experimental results are described by Lungmiur isotherm. The kinetic data were fitted to pseudo-first order kinetics, pseudo-second order kinetics and interparticle diffusion model. The kinetic adsorption data were best fitted by psuedo-second order kinetic.